I-V Curves of an Apigenin Dye and Their Analysis by a New Parabolic Function - Sanusi, Kayode; Ajayi, Olukayode S.; Borisade, Adegoke O.; Elusiyan, Regina B.; Yilmaz, Yusuf; Ceylan, Ümit (Frontiers in Chemistry, 2021)
A new parabolic function for I-V curves’ analysis has been proposed. The new “analytical tool” provides a simple way to describe photophysical processes at an approximately monolayer surface of a dye-sensitized solar cell. It may now be possible to estimate factors such as hole-electron recombination, surface defects and electron diffusion at the semiconductor layer. The theoretical approach previously reported by our group for photovoltaic performance prediction has also been validated, using experimental data derived from apigenin dye, together with DFT/TD-DFT calculations performed on this dye and the highly rated black dye.